Leadership in an interdependent world (The World Bank group WashingtonUS, 2003)
Presents addresses from the 4th conference of the Staff Exchange Program of the World Bank Group. Topics include: Leadership in an interdependent world; Accelerating the response to HIV/Aids in the Caribbean; and The role of democracy and institutionalization in the quest for development. Presenters include: Sir George Alleyne, The Hon. Dr Denzil Douglas, \n Dr Edward Greene, and The Hon. Dr Rex Nettleford.
Located in the LRC. 5 CDs. Leadership in an interdependent world (2 CDs); Accelerating the response to HIV/AIDS in the Caribbean (1); Role of democracy and institutionalization in the quest for development (1). 1 CD captures the sights and sounds of the Conference.